CULTURAL FACTORS IN LEARNING MATHEMATICS: THE CASE ON ACHIEVEMENT LEVEL AMONG BADJAO STUDENTS - Leomarich Casinillo; Maria Cecilia Camulte; Darwin Raagas; Teresita S. Riña (IJIET (International Journal of Indonesian Education and Teaching), 2020)
This study focused mainly on the cultural factors such as beliefs, value practices and exposure to technology-related instructional materials in learning mathematics in regards to their level of achievement among Badjao students. At present, there are limited studies on the learning factors in regards to the level of achievement in mathematics among Badjao students in Bato, Leyte, Philippines. The study employed 71 Badjao elementary and high school students in four selected schools in the municipality of Bato, Leyte using a complete enumeration. Descriptive statistics and Chi-square Contingency Coefficient were used to characterize the variables of interest and to capture its relationships, respectively. Result reveals that the belief of Badjao students is high which indicates that mathematics is important to their daily lives and well-being. However, when it comes to their value practices, Badjao students rated average, which implies that they have mediocre study habits towards mathematics. Findings revealed that almost all of the Badjao students are beginners in their proficiency level in learning mathematics. Result shows that there is a significant relationship between mathematics achievement of the Badjao students and their beliefs about mathematics as well as their value practices in learning mathematics. Furthermore, their level of achievement in mathematics and level of exposure to technology-related instructional materials has no relationships.